IRP commission: sexual minorities and mental health: global perspectives. (19th May 2022) - Bhugra, Dinesh; Killaspy, Helen; Kar, Anindya; Levin, Saul; Chumakov, Egor; Rogoza, Daniel; Harvey, Carol; Bagga, Harjit; Owino – Wamari, Yvonne; Everall, Ian; Bishop, Amie; Javate, Kenneth Ross; et al.
Abstract: Sexual orientation is a key determinant of the identity of human beings. It has also been seen as a social determinant of health. People whose sexual orientation is non-heterosexual or sexual minorities or sexually diverse are included in the broad umbrella term LGBT (Lesbian, Gay, Bisexual, and Transgender) which is a commonly used acronym in activism, social policy, and subsequently cultural literature. For this reason, this Commission focuses primarily on sexual orientation i.e. lesbian, gay and bisexual (LGB) groups. We have used terms non-heterosexual, sexual minorities or sexual variation interchangeably. We have not considered asexual individuals as research in the field is too limited. We are cognisant of the fact that topics relating to mental health and sexual orientation discussed in this Commission will intersect with other issues of personal, cultural and social identity, and will thus be relevant to individuals including many transgender individuals. The inclusion of mental health issues relevant to gender-diverse individuals as well as gender identity is important and deserves its own separate detailed discussion. The exact number of sexually diverse individuals in a population is often difficult to estimate but is likely to be somewhere around 5% of the population. Rates of various psychiatry disorders and suicidal ideation and acts of suicide in LGB populations are higher than general population and these have been attributed to minority stress hypothesis. Elimination of inequality in law can lead to reduction in psychiatric morbidity in these groups. However, these are all diverse groups but even within each group there is diversity and each individual has a distinct and unique experiences, upbringing, responses to their own sexual orientation, and generating varying responses from families, peers and friends as well as communities (including healthcare professionals). The mental healthcare needs of sexual minority individuals vary and these variations must be taken into account in design, development and delivery of healthcare and policies. Improving access to services will help engagement and outcomes and also reduce stigma. The commission recommends that there is no role for so-called conversion therapies and other recommendations are made for clinicians, researchers and policymakers.